1987
DOI: 10.1002/jcp.1041310109
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium deprivation inhibits the expression of differentiation‐related phenotypes in human promyelocytic leukemia HL‐60 cells

Abstract: The role of magnesium ions in the differentiation of human promyelocytic leukemia HL-60 cells was investigated. When HL-60 extracellular magnesium was deficient (less than 0.01 mM), the total intracellular magnesium content and [3H] leucine incorporation rates decreased to 61 and 28%, respectively, on day 3. When the cells were treated with various inducers (100 nM 1 alpha, 25 dihydroxyitamine D3 (1,25(OH)2D3), 100 nM beta-all-trans retinoic acid (RA), 20 nM 12-o-tetradecanoyl phorbol-13-acetate (TPA), 1.25% d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…However, as HL-60 cell proliferation is not coupled to its differentiation as we [3,22] and others [29,30] have previously demonstrated, the proliferationsuppressive effect of uremic serum could be neglected in assessing the effect of I,25-(OH)2D3 on cell differentiation. Although the Ca and Mg levels in the culture medium are known to affect the l,25-(OH)2Dr induced HL-60 cell dif ferentiation [31,32], we did not detect a significant dif ference in those levels between the uremics and the controls. Aluminium is known to cause l,25-(OH)2D3 resistance at a post-receptor step with a compensatory rise in the 1,25-(OH)2D3 receptor levels in target tissues [33].…”
Section: Discussioncontrasting
confidence: 35%
“…However, as HL-60 cell proliferation is not coupled to its differentiation as we [3,22] and others [29,30] have previously demonstrated, the proliferationsuppressive effect of uremic serum could be neglected in assessing the effect of I,25-(OH)2D3 on cell differentiation. Although the Ca and Mg levels in the culture medium are known to affect the l,25-(OH)2Dr induced HL-60 cell dif ferentiation [31,32], we did not detect a significant dif ference in those levels between the uremics and the controls. Aluminium is known to cause l,25-(OH)2D3 resistance at a post-receptor step with a compensatory rise in the 1,25-(OH)2D3 receptor levels in target tissues [33].…”
Section: Discussioncontrasting
confidence: 35%
“…Inasmuch as re-introduction of Mg in the culture medium enabled DMSO-treated cells to differentiate, the authors also concluded that Mg deprivation could compromise appearance of the differentiated phenotype but not of cell commitment to differentiation. Such conclusion can be tentatively reconciled with the well known inhibition of protein synthesis by Mg deprivation (54). Clearly, one might wonder whether such conditions are specific enough to probe the possible role of Mg in differentiation.…”
Section: The Effect Of Extracellular Mg On Cell Differentiationmentioning
confidence: 69%
“…Since we previously demonstrated that HL-60 cells could become committed to differentiation and yet not express the differentiation-related phenotypes in magnesium-deficient medium (Okazaki et al, 1987), the results obtained here suggested that int-DIA was present in 1,25(0H)2D3-treated HL-60 cells and could accumu- late in differentiation-committed phenotype-nonexpressing cells to a greater degree than it could in differentiation-committed phenotype-expressing cells.…”
Section: Effects On Cybrid Differentiation Of Fusion Between Untreatementioning
confidence: 64%
“…In the previous report, we showed that HL-60 cells treated in magnesium-deficient medium with optimal concentrations of various inducers including 1,25- (OH)2D3, RA, TPA, and actinomycin D were committed to differentiate but did not express the differentiationrelated phenotypes (Okazaki et al, 1987). Using this system, it has become possible to divide the process of HL-60 cell differentiation into at least two steps, namely differentiation-committed phenotype-nonexpressing and phenotype-expressing steps.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation